A review of Neotropical Axarus, with the description of five new species (Diptera: Chironomidae). (2nd September 2018) - Andersen, Trond; Donato, Mariano; Hagenlund, Linn K.; Mauad, Melina; Mendes, Humberto F.
ABSTRACT: The genus Axarus Roback, 1980 is known from the Australasian, Holarctic, and Neotropical regions. Five species are so far recognized from the Neotropical Region: A. corycus Mendes & Andersen, 2010, A. froehlichi Andersen & Mendes, 2002 and A. villosus Mendes & Andersen, 2010 from Brazil; A. ochros (Walley in Curran, 1934) from Guyana; and A. rogersi (Beck & Beck, 1958) from Costa Rica, Mexico, Nicaragua and Southeastern USA. Below we describe and figure an additional five new Axarus species from Argentina and Brazil based on male imagines. Of the five new species, the following three belong to the A. festivus species group: A. diabolicus Andersen, Mendes & Hagenlund sp. nov., A. globosus Donato, Mauad & Andersen sp. nov., and A. intervales Andersen, Mendes & Hagenlund sp. nov., while the two others, A. corgao Andersen, Mendes & Hagenlund sp. nov. and A. meloi Andersen, Mendes & Hagenlund sp. nov., belong to the A. rogersi species group. The generic description is emended to accommodate the new species and a key to the males of the Neotropical species is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:46B8DABB-D68A-4C6A-8D6F-D04DCA670A54